Hubungan Tingkat Pengetahuan Dengan Sikap Mahasiswi Keperawatan Tentang Vaksinasi HPV (Human Papilloma Virus) Di Kota Jayapura - Dwi Astuti; Hendry Kiswanto Mendrofa (STIKES Columbia Asia Medan, 2025)
The strategy for preventing cervical cancer includes primary prevention through the HPV (Human Papilloma Virus) vaccine, which is used to prevent cervical cancer, especially in women. The Ministry of Health has included HPV vaccination as a mandatory vaccine. This study aims to support government programs and identify the role of nurses as educators and consultants for nursing students. The objective of this research is to analyze the relationship between knowledge and attitudes of nursing students regarding HPV (Human Papilloma Virus) vaccination in Jayapura City. The research method used is an analytical orrelational survey with a retrospective design. The sampling technique applied was accidental sampling, involving 109 respondents. The results of this study indicate a relationship between the level of knowledge and the attitudes of nursing students regarding HPV (Human Papilloma Virus) vaccination in Jayapura City.